2022
DOI: 10.1002/leg3.178
|View full text |Cite
|
Sign up to set email alerts
|

Velvet bean (Mucuna pruriens): A sustainable protein source for tomorrow

Abstract: Protein is one of the essential major nutrients required for the cell functioning in human body. Complete proteins, which are usually found in animal‐based proteins, despite of having high biovailability also cause adverse effect on the environment and increased the risk of diet‐related chronic diseases. Recent years have witnessed enhanced awareness about the health benefits of substituting animal‐based proteins with plant‐based proteins, especially in developed countries. Nitrogen‐fixing grain legumes are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…A study reported soaking, boiling, roasting, milling, and several combinations of these as methods of processing Bambara groundnut in Zimbabwe (Mubaiwa et al, 2018). Another study presented conventional and advanced methods such as boiling, autoclaving, roasting, cracking, germination, irradiation, and sonication as processing methods for the effective utilization of velvet bean (Baby et al, 2022). Additional information collected by the survey revealed that the legumes were mostly used in savory dishes involving the inevitable addition of salt to impart the characteristic savory taste.…”
Section: Resultsmentioning
confidence: 99%
“…A study reported soaking, boiling, roasting, milling, and several combinations of these as methods of processing Bambara groundnut in Zimbabwe (Mubaiwa et al, 2018). Another study presented conventional and advanced methods such as boiling, autoclaving, roasting, cracking, germination, irradiation, and sonication as processing methods for the effective utilization of velvet bean (Baby et al, 2022). Additional information collected by the survey revealed that the legumes were mostly used in savory dishes involving the inevitable addition of salt to impart the characteristic savory taste.…”
Section: Resultsmentioning
confidence: 99%
“…(Mucuna pruriens) Crude protein (28.82 mg), Potassium (1,628.36 mg), Phosphorus (456.35mg), Calcium (689.45 mg), Iron (14.74 mg) and Magnesium (341.44 mg).Chinju et al,[22] 15.Tree Bean (Parkia roxburghii) Calcium (97.47 mg), Potassium (2400 mg), Copper (2.3 mg) and Zink (2.77 mg)Chatterjee et al,[23,[24-28] …”
mentioning
confidence: 99%